PENDIDIKAN KELUARGA DALAM PRESPEKTIF AL- QUR’AN - Nia Nia Juwita Purnika Sari; Hani Zahrani (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
Family Education can be interpreted as the efforts and efforts of parents in providing guidance, direction, coaching and the formation of the child's personality as well as providing provision of knowledge to children. The basis of family education, namely the family environment is the first environment and the family is the first education that is ready to face the stages of development until reaching adulthood. Family education is the responsibility of everyone to protect themselves and their families from the fires of hell, and are required to do what is imposed and get rid of what which is prohibited, not only for himself but also must teach the family. The purpose of this research is to describe family education in the perspective of the Qur'an. The type of research used is a theoretical review or literature review with a descriptive approach. Data collection techniques using documentation review and data analysis techniques with content analysis by utilizing the literature. The results of this study, we as parents need to instill the values of religious education in children. Family education in the perspective of the Koran that must be taught is education of faith, worship and morals. From the verses of the Qur'an, the method of family education is explained by exemplary methods, advice, habituation, rewards and punishments.